PENGARUH RESPONSIVENESS, TANGIBLE, DAN EMPHATY TERHADAP KEPUASAN PELAYANAN PELANGGAN PADA PT. PLN (Persero) DI KABUPATEN ENREKANG - Hamzyah Hamzyah (Universitas Muhammadiyah Makassar, 2019)
Data analysis technique used in this research is multiple linear regression. To explain the description of research related to the hypothesis by using analysis: Test Validity, Test Reliability, t Test (Partial), Test F (Simultaneous). Based on the results of data analysis shows that Responsiveness (X1), Tangible (X2) and Empathy (X3), have a positive and significant effect on Customer Satisfaction (Y) shown by the value of correlation coefficient of 27.802. As for the significant test of t test that the tcount obtained is for the responsiveness variable (X1) tcount (2,212) ttable (1.98472) at 5% significance level meaning positive and significant effect on customer service satisfaction (Y), tangible tcount (6.757 ) ttabel (1,98427) at 5% significance level meaning positive and significant influence to customer service satisfaction (Y), empathy tcount (3,295) ttabel (1,98472) at 5% significance level meaning positive and significant to satisfaction customer service (Y). Tangible is the dominant variable influencing customer service satisfication based on standardized coefficients with a beta value of 0,523 or 52,3%.